Culturally contextualized suicide prevention for international students: new opportunities for research and practice - McKay, Samuel; Meza, Jocelyn I. (Frontiers in Psychology, 2024)
The rising incidence of suicide-related thoughts and behaviors among international students presents a significant public health challenge and growing concern among college campuses. Current intervention strategies often rely on Western-centric and colonized approaches developed and tested with primarily Western, Educated, Industrialized, Rich and Democratic (WEIRD) samples. Exclusion and historical underrepresentation of ethnoracially minoritized groups in suicide prevention treatment trials create gaps in advancing our science because they often miss the cultural contextualization crucial for effective prevention and intervention in diverse groups from different countries of origin. To address the limitations of these Western-centric strategies, we explored existing prevention recommendations and approaches through the lens of an expanded version of the newly developed Protective Factors Framework, tailored for non-Western cultural perspectives. We propose significant opportunities for enhancing current practices and point to promising future directions. The primary areas for development include: (1) bolstering community empowerment and ownership, (2) refining mechanisms of change to encompass multicultural viewpoints, and (3) focusing on effective implementation and thorough evaluation for ongoing refinement. This methodology not only shows promise for enhancing international student suicide prevention but also offers insights for broader application in suicide prevention among other culturally diverse populations.